A LEGAL REVIEW OF CUSTOMARY MARRIAGE IN THE VILLAGE OF GUMANTAR, WITH PARTICULAR REFERENCE TO THE LAW OF MARRIAGE - Wahyudin, Wahyudin; Syahrial Haq, Hilman; Amalia, Fitriani (Universitas Muhammadiyah Mataram, 2024)
This research aims to ascertain the historical and procedural aspects of merarik custom in Gumantar Village, Kayangan District, North Lombok Regency. In order to achieve this, the research will examine the following: